Impact of written corrective feedback on Malaysian ESL secondary students’ writing performance - Malini Ganapathy,; Tan, Debbita Ai Lin; Phan, Jonathan (Penerbit Universiti Kebangsaan Malaysia, 2020)
The teacher plays a crucial role in providing good written corrective feedback (WCF), especially in Malaysia’s education system. Numerous studies were conducted on its effectiveness and students’ perceptions, but most were meant for tertiary education. This mixed method study identified the types of WCF provided by teachers during their English as a Second Language (ESL) writing pedagogical practices in five Malaysian secondary schools, and analysed the perceptions of 482 students and 15 teachers towards the provision of WCF. A questionnaire survey was administered to collect quantitative data from students, and focus group discussions were conducted among the teachers to collect qualitative data. Students highlighted that, teachers gave unfocused, metalinguistic WCF, and only held discussions much later. Students preferred teachers to mark all errors, and perceived WCF as important in improving their writing skills. Teachers reported, that they are in the habit of providing unfocused, indirect, and metalinguistic WCF, and held discussions with students only after marking the scripts. They perceived WCF as beneficial in enhancing students’ writing skills and teachers’ pedagogical practices. In this vein, it is construed, that the perceptions of teachers and students are mostly aligned. Teachers need to be aware of the existing types of WCF and incorporate the appropriate ones in their teaching practices. This study is significant in enriching ESL teachers’ pedagogical practices of teaching writing to secondary school students by providing the best practices of WCF, taking into account students’ interest, and ultimately create a more significant impact in the ESL writing classroom.